Recent development in fluorescent probes for copper ion detection - Ali, Mukhtiar; Memon, Najma; Ali, Manthar; Chana, Abdul Sami; Gaur, Rashmi; Jiahai, Ye (Current topics in medicinal chemistry, 2022)
Copper is the third most common heavy metal and an indispensable component of life. Variations of body copper levels, both structural and cellular, are related to a number of disorders; consequently, pathophysiological importance of copper ions demands the development of sensitivity and selective for detecting these organisms in biological systems. In recent years, the area of fluorescent sensors for detecting copper metal ions has seen revolutionary advances. Consequently, closely related fields have raised awareness of several diseases linked to copper fluctuations. Further developments in this field of analysis could pave the way for new and innovative treatments to combat these diseases. This review reports on recent progress in the advancement of three fields of fluorescent probes; chemodosimeters, near IR fluorescent probes, and ratiometric fluorescent probes. Methods used to develop these fluorescent probes and the mechanisms that govern their reaction to specific analytes and their applications in studying biological systems, are also given.